Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This question is from Folland 6.38, Show that $f \in L^p $ iff $\sum_{k=-\infty}^ {\infty} 2^{pk} \mu \{{x: |f(x)|>2^{k}}\} \lt \infty$

  1. If $f \in L^p $, I applied the Chebyshev's inequality
  2. But for the other direction, I don't know how to begin.

Any advice would be appreciated. Thanks

share|cite|improve this question
up vote 4 down vote accepted

On $E_k = \{ 2^k < \left| f(x) \right| \leq 2^{k+1} \}$, we have

$$ 2^{pk} < \left|f(x)\right|^{p} \leq 2^{p(k+1)}.$$

Thus integrating on $E_k$ we have

$$ 2^{pk} \mu (E_k) < \int_{E_k} \left|f(x)\right|^{p} \, d\mu \leq 2^{p(k+1)} \mu(E_k).$$

Summing through $k$, we obtain

$$ \sum_{k=-\infty}^{\infty} 2^{pk} \mu (E_k) < \int \left|f(x)\right|^{p} \, d\mu \leq 2^{p} \sum_{k=-\infty}^{\infty} 2^{pk} \mu(E_k).$$

Finally, note that

$$ \sum_{j=-\infty}^{k} 2^{pj} = \frac{2^{kp}}{1 - 2^{-p}}. $$

Thus we have

$$ \begin{align*} \sum_{k=-\infty}^{\infty} 2^{pk} \mu (E_k) &= (1 - 2^{-p}) \sum_{k=-\infty}^{\infty} \sum_{j=-\infty}^{k} 2^{jp} \mu (E_k) \\ &= (1 - 2^{-p}) \sum_{j=-\infty}^{\infty} \sum_{k=j}^{\infty} 2^{jp} \mu (E_k) \\ &= (1 - 2^{-p}) \sum_{j=-\infty}^{\infty} 2^{jp} \mu \{ 2^j < \left| f(x) \right| \}. \end{align*}, $$

from which the conclusion follows.

share|cite|improve this answer

Note that $$\int|f|^pd\mu=p\int_0^\infty t^{p-1}\mu\{x:|f(x)|>t\}dt$$ and $$\int_{2^k}^{2^{k+1}}t^{p-1}\mu\{x:|f(x)|>t\}dt\le 2^{(k+1)p}\mu\{x:|f(x)|>2^k\}.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.